Evaluación del desempeño de sistemas de televisión digital directa por satélite - Matos Gómez, Jorge (Ingeniería, 2000)
Direct satellite TV systems operating in FSS and BSS Ku-bands ( 12 GHz band ) are affected by a g roup of phenomena in troposphere and ionosphere, being rain the most important one (attenuation and noise increment). Although it is shown in [1] some general results that can be applied to satellite link budgets, it has not been taken into consideration the possible occurrence of fading. This paper shows an engineering procedure that allows the performance evaluation in downlink satellite links. The procedure is compared with the recommended receiver antenna diameters in Berlin , receiving digital television signals (standard DVB-S ) from ASTRA 1.A.The maximum error is 1.5 % showing the method's confidence. The ITU-R method is used in rain attenuation calculations Although the method is directly applied to Ku-band, it can be extended to C-band where rain has lesser influence.